2014
DOI: 10.1111/1744-7917.12132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food quality on trade‐offs among growth, immunity and survival in the greater wax mothGalleria mellonella

Abstract: The resources available to an individual in any given environment are finite, and variation in life history traits reflect differential allocation of these resources to competing life functions. Nutritional quality of food is of particular importance in these life history decisions. In this study, we tested trade-offs among growth, immunity and survival in 3 groups of greater wax moth (Galleria mellonella) larvae fed on diets of high and average nutritional quality. We found rapid growth and weak immunity (as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 75 publications
4
65
0
Order By: Relevance
“…DeBlock and Stoks, 2008) and others an increase (e.g. Krams et al, 2015). Food limitation levels varied across studies, making them difficult to compare.…”
Section: Network Reconfiguration In Other Systemsmentioning
confidence: 99%
“…DeBlock and Stoks, 2008) and others an increase (e.g. Krams et al, 2015). Food limitation levels varied across studies, making them difficult to compare.…”
Section: Network Reconfiguration In Other Systemsmentioning
confidence: 99%
“…The nutritional balance, quantity and quality of food modulate an individual’s phenotype and also mediate trade-offs between life-history traits of consumers, including insects123 and vertebrates45. Nutritional and non-nutritional food components, such as plant secondary metabolites, modify the behaviour and mediate the development and health of consumers678.…”
mentioning
confidence: 99%
“…The nutritional bases of aging, starvation and desiccation resistance, and immune system function have been explored using insects as model organisms31113. Nutritional sciences, particularly nutritional ecology and physiology, have developed much of the present theoretical understanding based on studies with insects614.…”
mentioning
confidence: 99%
“…Males of many species tend to increase the number of copulations (Bateman 1948), and in case of terminal investment in reproduction male individuals may increase their sexual attractiveness at the expense of their longevity (Krams et al 2014b(Krams et al , 2015. In females, fitness is often positively linked to lifespan (Trivers 1972), while longevity largely depends on investment into immune function (Lin et al 1998;Krams et al 2014a). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies on invertebrates have recently demonstrated the role of ecological conditions on trade-offs between immune function and fecundity (Zerofsky et al 2005), availability of food (Moret and Schmid-Hempel 2000;Krams et al 2014aKrams et al , 2015, especially nitrogen-rich proteins, lifespan (Ye et al 2009;Krams et al 2013b) and larval competitive ability (Kraaijeveld and Godfray 1997). Selection for increased cuticular melanization in mealworm beetles Tenebrio molitor resulted in an increase in immune response (Armitage and Siva-Jothy 2005).…”
Section: Introductionmentioning
confidence: 99%